METHODS EMPOWERMENT SOUL ENTREPRENEURSHIP OF YATIM AND DHUAFA ORPHANAGE HAFIZIL YATAMU SABUNGAN JAE PADANGSIDIMPUAN - Windari W; Damri Batubara (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2021)
This Yatamu Hafizil Orphanage is a social foundation that educates and fosters entrepreneurial skills for orphans and poor people with social problems. Like economic capacity, left behind by dead father and mother. The theory explains, financial, entrepreneurial spirit, thinking, creative spirit, innovative are the core requirements for empowering the entrepreneurial spirit. Unlike the orphanage and poor people in Sabungan, Jae accepts children to be empowered for their entrepreneurial spirit at no cost. This is contrary to the requirements for empowering an entrepreneurial spirit. entrepreneurship requires sufficient capital, a strong physical condition, has a creative and innovative mindset. This research is a descriptive qualitative research. The data sources used are primary and secondary. The informant retrieval method used was purposive sampling, while the data collection techniques were observation, interview and documentation. The instrument used in the interview was a focus group discussion. The analysis of the validity of the data used was source triangulation. As a result, there are several methods of empowering the entrepreneurial spirit of the orphanage and poor people. Namely, snowballing lessons, meet the guests, town meetings, whatsapp conferences.